2006
DOI: 10.1021/nl060050n
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Underlying Specificity of Proteins Targeting Inorganic Materials

Abstract: Adhesion force analysis using atomic force microscopy clearly revealed for the first time the mechanism underlying the specific binding between a titanium surface and ferritin possessing the sequence of Ti-binding peptide in its N-terminal domain. Our results proved that the specific binding is due to double electrostatic bonds between charged residue and surface groups of the substrate. Furthermore, it is also demonstrated that the accretion of surfactant reduces nonspecific interactions, dramatically enhanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 33 publications
(46 reference statements)
6
123
1
Order By: Relevance
“…[147] It was suggested that the speci-ficity of binding was due to electrostatic interactions between peptide and surface groups of the titanium substrate. [148] This N-terminal extension is uniquely presented on the exterior surface of the ferritin cage and is readily altered by genetic manipulation.…”
Section: Ferritin: Exteriormentioning
confidence: 99%
“…[147] It was suggested that the speci-ficity of binding was due to electrostatic interactions between peptide and surface groups of the titanium substrate. [148] This N-terminal extension is uniquely presented on the exterior surface of the ferritin cage and is readily altered by genetic manipulation.…”
Section: Ferritin: Exteriormentioning
confidence: 99%
“…Adsorption of protein on various materials has been widely studied and it has been found that factors such as electrostatic interaction, hydrophobic interaction, hydrogen bonding, VDW interaction and specific chemical interactions between protein and the adsorbent play important roles [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. Short peptide sequences interact with TiO 2 surface via electrostatic interaction also [57][58][59].…”
Section: Adsorption Mechanism Of Rgdmentioning
confidence: 99%
“…7,8 Understanding water adsorption on TiO 2 is the key not only to efficiently split water molecules (as made use of in hydrogen gas production 9 ) but also to optimize adsorption on, and functionalization of, TiO 2 by larger molecules as mediated via strongly bound surface waters. [10][11][12][13][14][15] On the other hand, concerns have been raised with respect to environmental safety and health when TiO 2 is used in medical implants 16 and as engineered nanoparticles in consumer products. 17 TiO 2 nanoparticles are small enough to penetrate the blood-brain barrier, 18 can aggregate in organisms and the environment, and yield a nanotoxic response by increasing the levels of intracellular reactive oxygen species, leading to apoptosis.…”
Section: Introductionmentioning
confidence: 99%